Microbial erosion assessment on waterlogged archaeological woods (WAWs) from a Chinese ancient shipwreck, Nanhai No. 1 - Mengge Gao; Qinfen Zhang; Xinxin Feng; Dong Chen; Jian Sun; Yong Cui; Runlin Xu (Heritage Science, 2018)
Abstract This article aims at identifying the timber species of Nanhai No. 1, an ancient shipwreck (Song Dynasty, 800 years ago) sunk in the South China Sea, finding out the types of bacteria that corrode the wood components of the shipwreck and analyzing the erosion level. The changes of the internal structure of wood under different erosion degrees are described as well. With light microscope and electron microscope technology, the microscopic and submicroscopic structures of 20 wooden components from the shipwreck were investigated. The shipwreck was built of 6 timber species, including Pinus massoniana, Fokienia hodginsii, Terminalia hainanensis, Mischocarpus oppositifolius, Alnus trabeculosa and Mussaendopsis beccariana. Based on analyzing the traces left after bacterial erosion, it was determined that the erosive microbes in the sunken ship were mainly erosion bacteria and tunneling bacteria. According to the criteria from relevant literature, the analysis on the bacterial erosion degree of each wood sample shows that most of the wood components present weak to moderate erosion, except a few samples which are totally degraded. Comparison with the bacterial erosion on the wooden components of different ancient shipwrecks, sunk in different years in the southeast China, it is noticed that due to the different seabed environments (sunk conditions), the wood structure of the Nanhai No. 1 sunken ship is the best preserved although its sunken time is longer than the others. The silt-covered anaerobic environment could be one of the protective measures which preserves the ancient sunken ships.